The role of exercise in Suﬁ sm epistemological understanding of the Kazakh people (Journal of Philosophy Culture and Political Science, 2019)
Annotated: Suﬁ sm plays an important role in the cultural and religious knowledge of the Kazakh people. The essence of the understanding in the beginning of the Kazakh Muslimism took perfect personality of the Prophet Muhammad. The Quran and Sunnah of the teachings of Islamic Suﬁ sm initiative, which modeled the spiritual and empirical practice. Keywords: the teachings of Suﬁ sm, the Kazakh people, spiritually-empirical practice of Islam, spiritual horizons, the Islamic civilization.